Complementary and Alternative Medicine Use by Patients Chronically Infected with Hepatitis C Virus - Colin P White; Gerilynn Hirsch; Sunil Patel; Fatin Adams; Kevork M Peltekian (Canadian Journal of Gastroenterology)
Complementary and alternative medicine (CAM) is becoming increasingly popular in North America. The use of CAM is also popular in patients with chronic liver disease but is not well documented. The extent of use of CAM in chronic hepatitis C virus (HCV) infected patients was determined, and the demographic and clinical data between users and nonusers of CAM was compared.